2022
DOI: 10.1155/2022/5873218
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis and Evaluation Research on the Construction of the Music Art Management Curriculum System Based on the Deep Learning Model

Abstract: In view of the fact that music courses are seldom offered in schools and lack of management, there are many problems in the management system of music and art. In order to improve the learning effect of students in music courses, this paper proposes to build a music art management curriculum system based on the in-depth learning model. This paper puts forward the requirements of in-depth learning in music and art curriculum indicators and puts forward the model framework of music and art learning. Through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…is has improved a certain reference value and reference for the school's music teaching and management. Hu and Yang [16] have found that school music teaching has the problems of few courses and lack of music management. In order to improve students' interest in music learning, it uses deep learning technology to study its role in music teaching management.…”
Section: Related Workmentioning
confidence: 99%
“…is has improved a certain reference value and reference for the school's music teaching and management. Hu and Yang [16] have found that school music teaching has the problems of few courses and lack of music management. In order to improve students' interest in music learning, it uses deep learning technology to study its role in music teaching management.…”
Section: Related Workmentioning
confidence: 99%
“…Big data theory is also widely used in image recognition and video feature recognition, which also brings great convenience to people's life and production. In life, the characteristics of research objects in production or life are mainly divided into three types: spatial characteristics, temporal characteristics, and environmental characteristics [ 19 , 20 ]. It also has many corresponding algorithms.…”
Section: Introductionmentioning
confidence: 99%